2017
DOI: 10.1038/s41598-017-07271-z
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic exposure impels CD4 commitment in thymus and suppress T cell cytokine secretion by increasing regulatory T cells

Abstract: Arsenic is globally infamous for inducing immunosuppression associated with prevalence of opportunistic infection in exposed population, although the mechanism remains elusive. In this study, we investigate the effect of arsenic exposure on thymocyte lineage commitment and the involvement of regulatory T cells (Treg) in arsenic-induced immunosuppression. Male Balb/c mice were exposed to 0.038, 0.38 and 3.8 ppm sodium arsenite for 7, 15 and 30 days through oral gavage. Arsenic exposure promoted CD4 lineage comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 61 publications
2
15
0
Order By: Relevance
“…Particularly, male BALB/c mice exposed to 0.038, 0.38 and 3.8 ppm sodium arsenite for 7, 15 and 30 days through oral gavage showed a significant dose-dependent increase in the ThPOK expression levels in thymus, suggesting an impairment in the regulation of CD4+ T cells differentiation. In the spleen, As increased the number of CD4+ T cells and promoted their differentiation into Treg cells, however, a low secretion of IFN-γ, TNF-α, IL-12, IL-4, IL-5 and IL-10 cytokines was observed in splenocytes ( Gera et al 2017 ). Activation of NF-kB and downstream signaling was shown to induce As-associated immune suppression ( Choudhury et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, male BALB/c mice exposed to 0.038, 0.38 and 3.8 ppm sodium arsenite for 7, 15 and 30 days through oral gavage showed a significant dose-dependent increase in the ThPOK expression levels in thymus, suggesting an impairment in the regulation of CD4+ T cells differentiation. In the spleen, As increased the number of CD4+ T cells and promoted their differentiation into Treg cells, however, a low secretion of IFN-γ, TNF-α, IL-12, IL-4, IL-5 and IL-10 cytokines was observed in splenocytes ( Gera et al 2017 ). Activation of NF-kB and downstream signaling was shown to induce As-associated immune suppression ( Choudhury et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The disruption of arsenic on the immune inflammatory homeostasis was inseparable from the involvement of cytokines controlled by various immune cells [ 18 20 ]. Our research found that the classic inflammatory factor, Tnf - α , did not change at 1 and 3 months but declined at 12 months under 25 mg/L NaAsO 2 treatment as well as decreased at 3 and 12 months in the case of 50 mg/L NaAsO 2 exposure in mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cavassni et al 31 found significantly increased numbers of Treg cells after recovery from severe sepsis and this was related to increased tumour growth and the inhibition of the antitumor effects of CD8 + T cells. Exposure to environmental toxicants, such as arsenic, promotes the differentiation of Treg cells and thus prevents Th1- and Th2-related cytokine production and increases susceptibility to opportunistic infections, such as tuberculosis 32 , 33 . These findings suggest that increases in Treg cells inhibit effector T cell activity and contribute to the development of immunosuppressive microenvironments, thus resulting in adverse health effects, such as immune evasion and cancer progression 34 36 .…”
Section: Introductionmentioning
confidence: 99%